Faktor-Faktor yang Berhubungan dengan Status Gizi pada Balita di Wilayah Kerja Puskesmas Tarus Kabupaten Kupang - Ina Finolia Lao; Anna Henny Talahatu; Utma Aspatria (Yayasan Literasi Sains Indonesia, 2025)
Nutritional status is a condition caused by the balance between nutrient intake from food and nutrient needs in the body. The study aims to determine factors related to nutritional status in the working area of ​​Tarus Health Center, Kupang Regency. This type of research is an analytical survey using a cross-sectional design. This study was conducted for 1 month. The population in the study were all toddlers in the working area of ​​Tarus Health Center with a sample size of 94 toddlers. Data analysis used the chi-square test. The sampling method in the study used the stratified random sampling technique. The results showed that the related factors were maternal nutritional knowledge (height/age p value = 0.000, weight/age p value = 0.001), feeding patterns (height/age p value = 0.001, OR = 4.718, weight/age p value = 0.003), history of exclusive breastfeeding (height/age p = 0.000, weight/age p value = 0.003) and provision of complementary feeding (height/age p value = 0.000, weight/age p value = 0.003,). While unrelated factors were maternal occupation (height/age p value = 0.783, weight/age p value = 1.000), food expenditure (height/age p value = 0.222, weight/age p value = 0.239) and history of LBW (height/age p value = 0.827, weight/age p value = 0.323). For mothers, pay more attention to the growth and development of toddlers by prioritizing nutritional fulfillment and being more active in visiting integrated health posts to obtain health services and be able to see the development of toddlers' health.